2022
DOI: 10.3168/jds.2021-21233
|View full text |Cite
|
Sign up to set email alerts
|

Whey fermented by Enterococcus faecalis M157 exhibits antiinflammatory and antibiofilm activities against oral pathogenic bacteria

Abstract: The aim of the present study was to investigate the antiinflammatory and antibiofilm effects of whey fermented by Enterococcus faecalis M157 (M157-W) against oral pathogenic bacteria. The M157-W significantly inhibited IL-1β, IL-6, and nitric oxide induced by the lipopolysaccharide of Porphyromonas gingivalis in RAW 264.7 cells. The M157-W also inhibited the production of IL-1β and IL-8 in human periodontal ligament cells. Treatment with M157-W suppressed the phosphorylation of mitogen-activated protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
2
3
0
1
Order By: Relevance
“…Further, the CLSM analysis also revealed that co-treatment of S. mutans MTCC 890 bacterial cells with PMs PS-74 resulted in a dramatic transference of staining patterns with a strong increase of dead bacteria. These results align with a previous study by Dahyun Song et al (2022) which showed that CLSM confirmed S. mutans biofilm was less dense because of the presence of M157-W. More recently, L. plantarum showed an inhibitory effect on the biofilm formation and the growth of S. mutans (Ślebioda et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Further, the CLSM analysis also revealed that co-treatment of S. mutans MTCC 890 bacterial cells with PMs PS-74 resulted in a dramatic transference of staining patterns with a strong increase of dead bacteria. These results align with a previous study by Dahyun Song et al (2022) which showed that CLSM confirmed S. mutans biofilm was less dense because of the presence of M157-W. More recently, L. plantarum showed an inhibitory effect on the biofilm formation and the growth of S. mutans (Ślebioda et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The anti-inflammatory properties of whey fermented by Enterococcus faecalis M157 against oral cavity pathogens were estimated [ 104 ]. Bacterial pathogens cause chronic inflammation leading to periodontitis in the oral cavity, Porphyromonas gingivalis being the main causative.…”
Section: Bacteria and Yeasts With Anti-inflammatory Properties In Foodmentioning
confidence: 99%
“…The M157 strain successfully inhibited IL-1β, IL-6, and induced NO of Porphyromonas gingivalis in RAW 264.7 cells. IL-6 and IL-8 in human periodontal ligament cells were also inhibited [ 104 ].…”
Section: Bacteria and Yeasts With Anti-inflammatory Properties In Foodmentioning
confidence: 99%
“…Ent. faecalis CAUM157 was recently implemented for postbiotic development through whey bioconversion to alleviate periodontitis in mouse models and investigate its anti-in ammatory and antibio lm effects against oral pathogens [30,31]. These studies demonstrated the protective properties and antimicrobial activities of M157 bacteriocins which provides evidence of their value and potential as a postbiotic product.…”
Section: Introductionmentioning
confidence: 97%